Impact of Critical Care Point-of-Care Ultrasound Short-Courses on Trainee Competence. Issue 9 (September 2019) - Rajamani, Arvind; Miu, Michelle; Huang, Stephen; Elbourne-Binns, Henry; Pracher, Florian; Gunawan, Sutrisno; Lakshmanan, Ramanathan; Flynn, Gordon; Sasidaran, Kandasamy; Subasinghe, Shyama; Parmar, Jinal; Hyunh, Trieu
Abstract : Objectives: Competence in point-of-care ultrasound is recommended/mandated by several critical care specialties. Although doctors commonly attend point-of-care ultrasound short-courses for introductory training, there is little follow-up data on whether they eventually attain competence. This study was done to determine the impact of point-of-care ultrasound short-courses on point-of-care ultrasound competence. Design: Web-based survey. Setting: Follow-up after point-of-care ultrasound short-courses in the Asia-Pacific region. Subjects: Doctors who attended a point-of-care ultrasound short-course between December 2015 and February 2018. Interventions: Each subject was emailed a questionnaire on or after 6 months following their short-course. They were asked if they had performed at least 30 structured point-of-care ultrasound scans and/or reached point-of-care ultrasound competence and their perceived reasons/challenges/barriers. They were also asked if they used point-of-care ultrasound as a clinical diagnostic aid. Measurements and Main Results: The response rate was 74.9% (182/243). Among the 182 respondents, only 12 (6.6%) had attained competence in their chosen point-of-care ultrasound modality, attributing their success to self-motivation and time management. For the remaining doctors who did not attain competence (170/182, 93.4%), the common reasons were lack of time, change of priorities, and less commonly, difficulties in accessing an ultrasound machine/supervisor. Common suggestions to improve short-courses included requests for scanning practice on acutely ill ICU patients and prior information on the challenges regarding point-of-care ultrasound competence. Suggestions to improve competence pathways included regular supervision and protected learning time. All 12 credentialled doctors regularly used point-of-care ultrasound as a clinical diagnostic aid. Of the 170 noncredentialled doctors, 123 (72.4%) reported performing unsupervised point-of-care ultrasound for clinical management, either sporadically (42/170, 24.7%) or regularly (81/170, 47.7%). Conclusions: In this survey of doctors attending point-of-care ultrasound short-courses in Australasia, the majority of doctors did not attain competence. However, the practice of unsupervised point-of-care ultrasound use by noncredentialled doctors was common. Further research into effective strategies to improve point-of-care ultrasound competence is required. Abstract : Supplemental Digital Content is available in the text.